Legal Protection of E-Book Copyright Based on Law No. 28 of 2014 on Copyright - Damri, Damri; Erniwati, Erniwati; Fitri, Aidil (Fakultas Hukum Dehasen, 2025)
vulnerable to copyright infringement, such as unauthorized reproduction and distribution. The problems that arise include: How is legal protection for e-book copyrights regulated under Indonesian positive law, and what are the legal sanctions for the misuse of e-book copyrights? This research uses a normative juridical approach and examines applicable legal provisions, particularly Law No. 28 of 2014 on Copyright and Article 25 of the Electronic Information and Transactions (ITE) Law. The results show that e-books are protected as literary works, and authors possess moral rights as regulated in Article 5 of the Copyright Law, as well as economic rights as stipulated in Articles 8 to 11. Legal protection is divided into two forms: preventive and repressive, with criminal sanctions regulated in Article 113 of Law No. 28 of 2014, civil sanctions in Article 95 paragraphs (1) and (2), and administrative sanctions for violators as regulated by the Regulation of the Minister of Communication and Informatics of the Republic of Indonesia No. 5 of 2020. Strict law enforcement and public awareness of the importance of respecting copyright are key to creating a fair and sustainable digital ecosystem.